2014
DOI: 10.1017/s0029665114000986
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fortification of cow's milk as a dietary strategy to increase dietary vitamin D intakes

Abstract: The majority of vitamin D required by humans is derived by ultraviolet (UV) radiation of the 7-dehydrocholesterol in the skin (1) . Vitamin D can also be obtained from the diet, and these sources of vitamin D are of particular importance here in the UK and Ireland as a number of factors, including age, skin pigmentation, clothing and the use of sun protection, and geographical location, negatively influence the skin's ability to synthesise the vitamin (2) . Milk is a source of naturally occurring vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…Both of these strategies would increase mean intakes of vitamin D to >10 lg day À1 at all ages at the same time reducing the prevalence of inadequate intakes to <25% for 1-and 2-year-old children and <40% for 3-and 4-year-old children. Our findings are in agreement with other studies in young children across the world that have shown that fortifying CM, providing vitamin D supplements or replacing CM with GUM would be effective strategies for increasing vitamin D intakes and status and improving the prevalence of inadequate intakes (16,17,(22)(23)(24)38,50) . Similar dietary modelling approaches using data from the National Diet and Nutrition Survey in the UK have shown that fortifying CM (50) and replacing CM with young child formula (38) would be effective strategies for increasing intakes and improve status of vitamin D at a population level.…”
Section: Vitamin Dsupporting
confidence: 92%
See 2 more Smart Citations
“…Both of these strategies would increase mean intakes of vitamin D to >10 lg day À1 at all ages at the same time reducing the prevalence of inadequate intakes to <25% for 1-and 2-year-old children and <40% for 3-and 4-year-old children. Our findings are in agreement with other studies in young children across the world that have shown that fortifying CM, providing vitamin D supplements or replacing CM with GUM would be effective strategies for increasing vitamin D intakes and status and improving the prevalence of inadequate intakes (16,17,(22)(23)(24)38,50) . Similar dietary modelling approaches using data from the National Diet and Nutrition Survey in the UK have shown that fortifying CM (50) and replacing CM with young child formula (38) would be effective strategies for increasing intakes and improve status of vitamin D at a population level.…”
Section: Vitamin Dsupporting
confidence: 92%
“…Our findings are in agreement with other studies in young children across the world that have shown that fortifying CM, providing vitamin D supplements or replacing CM with GUM would be effective strategies for increasing vitamin D intakes and status and improving the prevalence of inadequate intakes (16,17,(22)(23)(24)38,50) . Similar dietary modelling approaches using data from the National Diet and Nutrition Survey in the UK have shown that fortifying CM (50) and replacing CM with young child formula (38) would be effective strategies for increasing intakes and improve status of vitamin D at a population level. The recent Kimi trial in Germany also found that the daily consumption of vitamin D fortified GUM in children aged 2-6 years prevented the decrease in serum 25(OH)D concentrations typically noted in the winter and could be an effective measure for improving vitamin D status in a young population (16) .…”
Section: Vitamin Dsupporting
confidence: 92%
See 1 more Smart Citation